ECM-Regulator timp Is Required for Stem Cell Niche Organization and Cyst Production in the Drosophila Ovary - Pearson, John R.; Zurita, Federico; Tomas-Gallardo, Laura; Diaz-Torres, Alfonsa; Del Carmen Diaz De La Loza, Maria; Franze, Kristian; Martin-Bermudo, Mara D.; Gonzalez-Reyes, Acaimo (PLoS Genetics, 2016)
The extracellular matrix (ECM) is a pivotal component adult tissues and of many tissue-specific stem cell niches. It provides structural support and regulates niche signaling during tissue maintenance and regeneration. In many tissues, ECM remodeling depends on the regulation of MMP (matrix metalloproteinase) activity by inhibitory TIMP (tissue inhibitors of metalloproteinases) proteins. Here, we report that the only Drosophila timp gene is required for maintaining the normal organization and function of the germline stem cell niche in adult females. timp mutant ovaries show reduced levels of both Drosophila Collagen IV α chains. In addition, tissue stiffness and the cellular organization of the ovarian niche are affected in timp mutants. Finally, loss of timp impairs the ability of the germline stem cell niche to generate new cysts. Our results demonstrating a crucial role for timp in tissue organization and gamete production thus provide a link between the regulation of ECM metabolism and tissue homeostasis.
CRIS-Team Scopus Importer:2020-08-12